CONSIDERATIONS ON THE INFLUENCE OF THE TECHNOLOGICAL AND CLINICAL FACTORS IN THE AESTHETICS OF THE REMOVABLE PROSTHESES - Irina Gradinaru; Loredana Hurjui; Georgiana Macovei; Ion Hurjui; Magda-Ecaterina Antohe (Romanian Dental Association for Education, 2019)
The research confirms that someone's beauty considerably influences one's judgment, attitude and the estimated preferences of the others. From this perspective, the goal is to make the aesthetic restorative dental to appear as being natural. Natural teeth and artificial ones must be in harmony with the personality, age and sex of the patient.Partial removable dentures is part of aesthetic dental restorations which is most often neglected. Because the emphasis in the contemporary medical practice dentistry on the aesthetic dentistry and the progress that have taken place in the last 15 years in this area, patients require prosthetic that not only should be comfortable, but must be as little visible and as close to the natural look.